Differential effects of nematode infection on pollinating and non‐pollinating fig wasps: Can shared antagonism provide net benefits to a mutualism?. Issue 7 (10th May 2021) - Van Goor, Justin; Piatscheck, Finn; Houston, Derek D.; Nason, John D.
Abstract: Species pairs that form mutualistic associations are also components of broader organismal community networks. These interaction networks have shaped the evolution of individual mutualisms through interspecific interactions ranging from secondarily mutualistic to intensely antagonistic. Our understanding of this complex context remains limited because characterizing the impacts of species interacting with focal mutualists is often difficult. How is the fitness of mutualists impacted by the co‐occurring interactive network of community associates? We investigated this context using a model interaction network comprised of a fig and fig wasp mutualist, eight non‐pollinating fig wasp (NPFW) antagonists/commensals and a nematode previously believed to be associated only with the pollinator wasp mutualist. Through repeated sampling and field observations, we characterized the ecological roles of these mutualist‐associated organisms to identify key antagonists. We then investigated how potential nematode infection of NPFWs could impact wasp survival across key life stages and, in turn, inferred how this influences the fitness of the fig–pollinator mutualists. Unexpectedly, we found all Ficus petiolaris ‐associated NPFWs to be the targets for nematode infection, with infection levels sometimes exceeding that of pollinators. Experimental data collected for the most abundant NPFW species suggest that nematode infection significantly reduces their longevity. Further, comparisons of nematode loads for emerging and successfully arriving NPFWs suggest that infection severely limits their dispersal ability. Through these observations, we conclude that this infection could impact NPFWs more severely than either mutualistic partner, suggesting a novel role of density‐dependent facultative mutualism between figs, pollinator wasps and the nematode. This antagonist‐mediated suppression of other network antagonists may present an ecologically common mechanism through which antagonists can present net benefits for mutualists' fitness. Abstract : This article is the first to describe the phenomenon of nematode infection of non‐pollinating fig wasp taxa and its possible role in modulating network dynamics in fig–fig wasp communities. Similar facultative mutualisms may be more widespread than currently appreciated in other Arthropod‐rich community assemblages with shared resources in ephemeral environments.